A descriptive analysis of fifth-grade students’ creative thinking skills in solving perimeter problems of plane figures - Teti Husniati; Atep Sujana Atep; Encep Supriatna Encep; Supriadi Supriadi (CV. FOUNDAE, 2026)
Background: Creative thinking plays a central role in mathematics learning, especially in geometry, where students are required to explore various solution strategies and explain their reasoning clearly. Nevertheless, many elementary students still encounter difficulties in expressing and developing their mathematical ideas when solving problems. Aims: This study aims to provide a descriptive account of fifth-grade students’ creative thinking skills in solving perimeter problems of plane figures, viewed through the indicators of fluency, flexibility, originality, and elaboration. Method: The research employed a descriptive quantitative design involving 24 fifth-grade students. Data were gathered through an open-ended test constructed to reflect the four indicators of creative thinking. Students’ responses were scored using an assessment rubric, and the results were examined through descriptive statistical analysis, including the mean, score range, and standard deviation. Results: Students’ scores ranged from 21 to 84, with a mean of 54.2 (SD = 15.6), indicating that overall creative thinking performance was relatively low. Only 29.2% of students reached the predetermined mastery criterion. Among the four indicators, originality emerged as the strongest aspect, whereas elaboration showed the lowest achievement, revealing students’ challenges in expanding and detailing their ideas Conclusion: The findings suggest that students’ creative thinking skills in perimeter problem solving require further development, particularly in elaborating mathematical reasoning. Strengthening open-ended and reasoning-oriented instructional practices may help enhance creative engagement in geometry learning.